2006
DOI: 10.1016/j.jacc.2005.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Left Ventricular Function After Drug-Eluting Stent Implantation for Chronic Total Coronary Occlusions

Abstract: Drug-eluting stent implantation for a CTO has a beneficial effect on left ventricular volumes and function that can be predicted by performing MRI before revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(122 citation statements)
references
References 23 publications
6
107
1
6
Order By: Relevance
“…In observational studies, CTO-PCI resulted in left ventricular function improvement 13 ; however, the only randomized-controlled prospective clinical trial of CTO-PCI versus medical therapy reported to date, the evaluating Xience and left ventricular functionin PCI on occlusions after STEMI (EXPLORE) trial, did not show any difference in ejection fraction at 4 months post-procedure among patients with recent ST-segment elevation, acute myocardial infarction (MI), and a concomitant CTO in the noninfarct artery.…”
Section: N Benefits Of Cto-pcimentioning
confidence: 96%
“…In observational studies, CTO-PCI resulted in left ventricular function improvement 13 ; however, the only randomized-controlled prospective clinical trial of CTO-PCI versus medical therapy reported to date, the evaluating Xience and left ventricular functionin PCI on occlusions after STEMI (EXPLORE) trial, did not show any difference in ejection fraction at 4 months post-procedure among patients with recent ST-segment elevation, acute myocardial infarction (MI), and a concomitant CTO in the noninfarct artery.…”
Section: N Benefits Of Cto-pcimentioning
confidence: 96%
“…Наибольшей информативностью в диагно-стике жизнеспособного миокарда обладают ПЭТ с 18 F-ФДГ-фтордезоксиглюкозой ( 18 F-ФДГ) и МРТ с оценкой позднего контрастирования [2,[5][6][7]. Лишь небольшое число зарубежных исследований посвящено аналитическому сопоставлению про-гностической ценности вышеупомянутых методов в предсказании улучшения регионарной функции ЛЖ у пациентов с ИБС [6][7][8], а целенаправленное изучение их диагностической эффективности у больных с ХОКА ранее не выполнялось. Цель: сравнить информативность и прогностиче-скую ценность ПЭТ и МРТ сердца в предсказании обратимости регионарной систолической дисфунк-ции миокарда ЛЖ после эндоваскулярной реканали-зации окклюзированной коронарной артерии.…”
Section: оригинальные статьиunclassified
“…По данным литературы, ранее уже предпринима-лись попытки определения минимального порого-вого значения для показателей величины постин-фарктного рубца [7][8][9]. В зарубежной практике для предсказания улучшения регионарной сократимости используется критерий "глубина рубца".…”
Section: оригинальные статьиunclassified
“…Furthermore, successful CTO PCI increases hyperemic and resting myocardial blood low with enhanced regional contractility already 24 h after the procedure [43]. Patients with an infarction and a transmural involvement < 25% assessed by MRI show signiicant improvements in segmental wall thickening and a reduction of mean end-systolic and end-diastolic volumes after CTO PCI [44]. Finally, the diagnostic accuracy of pre-procedural contrast enhanced MRI in patients with CTO to detect myocardial infarction and to predict improvement of myocardial function after revascularization seems to be beter by using a combined viability analysis rather than focusing on the widely used transmural extent of infarction [45].…”
Section: Myocardial Viability and Left Ventricular Functionmentioning
confidence: 99%
“…High procedural success rates in conjunction with low complication rates improve risk/beneit ratio and are paramount for the acceptance and dissemination of CTO PCI. Successful CTO recanalization has the ability to relieve angina [71], reduce ischemia [41] and the need for CABG [72], improve exercise tolerance [73], electrical stability [74], left ventricular function [44], and tolerance of future ACS [13,75], and possibly survival [76,77] with a similar risk compared to regular PCI of non-CTO lesions [3]. Table 1 summarizes the rationale for CTO PCI.…”
Section: Indications For Cto Pcimentioning
confidence: 99%